Stratified analysis of satellite imagery of SW Europe during summer 2003: the differential response of vegetation classes to increased water deficit - A. Lobo; P. Maisongrande (Hydrology and Earth System Sciences, 2006)
The extraordinarily warm and dry summer experienced in SW Europe in 2003 provides an interesting case study for the analysis of the response of regional-scale vegetation variables to drier and hotter conditions. SW Europe includes a boundary between phytogeographic and climatic regions (Oceanic and Mediterranean) that differ in terms of summer precipitation, which let us compare the response of different vegetation types. In addition, some scenarios predict summer conditions such as those of 2003 to be common by the latter decades of the 21st century in this region. We have analyzed a monthly series of regional fields of normalized difference vegetation index from the VEGETATION-SPOT5 instrument, from 1999 to 2003. We show that negative anomalies of vegetation index in summer 2003 were larger for herbaceous vegetation of the Oceanic climate region and for deciduous forests. The vegetation index of August 2003 in the Mediterranean climate region was also significantly lower than normal values in August 1999–2002, albeit the anomalies were small in absolute value. We compared August NDVI, as a measure of the vegetation response, to the difference between total summer precipitation and total summer potential evapotranspiration, as a measure of atmospheric water stress. Our results indicate that water stress is a major factor structuring the geographic variability of NDVI in this region. In accordance with these results, the analysis of the data of 2003 indicate that the increased water stress was a key factor of the observed anomalies of vegetation index.